The Hardy boys the Mickey Mouse Club, 1956-1957 - Considine, Tim; Kirk, Tommy; Buena Vista Home Entertainment (Firm); Disney DVD (Firm) (Burbank, Calif Disney DVD Distributed by Buena Vista Home Entertainment, 2006)
Capture all the excitement of The Hardy Boys: The Mystery of the Applegate Treasure, which debuted on the first day of The Mickey Mouse Club's second season
Episodes in black and white; introd. sequences and special features in color
Title from container
1
Keywords: Hardy Boys (Fictitious characters) -- Drama; Hardy Boys (Fictitious characters) -- Juvenile films; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs